Modal Sosial Masyarakat Dalam Pelestarian Hutan Mangrove di Desa Kurau Barat, Kabupaten Bangka Tengah - Budi Darmawan Budi; Ariandi A. Zulkarnain; Irvan Ansyari (Universitas Halu Oleo (UHO), 2023)
Abstract This research was conducted with the aim of explaining the social capital carried out by the community in the conservation of mangrove forests in Kurau Barat Village, Bangka Tengah Regency. This study used a qualitative descriptive approach. The data collection process was conducted through interviews, observations, and documentation. The results of this research show that thanks to social capital, emphasizing trust, norms, and networks, the community is able to manage and preserve the mangrove forest in Kurau Barat Village collectively. Thus, the community not only benefits ecologically but also gains economic and social benefits. Efforts to build trust among the community have been successful, as community members have shown the ability to increase electability by emphasizing values such as hard work, honesty, and trust in fellow community members.